Environment-friendly ecological drainage plate capable of purifying air and preparation method of environment-friendly ecological drainage plate
By using zinc oxide-titanium dioxide-graphene nano-composite powder as a composite purification agent in environmentally friendly ecological filter boards, the problem of poor air purification effect of existing environmental pavement materials has been solved, and the efficient air purification effect and good effect are achieved Palace performance.
Patent Information
- Application Number
- CN202410974541.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-19
AI Technical Summary
The air purification effect of existing environmentally friendly road materials is limited, physical adsorption is reversible and may cause greater pollution, while the spectral range of photocatalysts is narrow and the air purification effect is poor.
The zinc oxide-titanium dioxide-graphene nano-composite powder is used as a composite purifier, and it integrates it into an environmentally friendly ecological filter plate through specific preparation methods to oxidize the harmful gas in the air in the air.
At the same time, the environmentally friendly ecological water filter plate has an efficient air purification effect while maintaining compressive strength, abrasion resistance and water permeability, and can effectively remove harmful gases such as nitrogen oxide and toluene.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application belongs to the field of environmentally friendly pavement technology, and specifically relates to an environmentally friendly ecological water filter board capable of purifying air and a preparation method thereof. Background Art
[0002] Permeable pavement is gradually gaining popularity, and many places are starting to build sponge cities to alleviate the problem of waterlogging. The main harmful components of automobile exhaust are NO x , HC compounds, CO, SO 2 In order to reduce the harm of automobile exhaust, one measure is to use environmentally friendly pavement materials that can purify the air for pavement. At present, there are two main purification mechanisms of environmentally friendly pavement materials: one is physical adsorption, but physical adsorption is reversible. When the adsorption is saturated, it will be released in situ, which may cause greater pollution; the other is to use photocatalysts to degrade harmful components in exhaust gas. Common photocatalysts include titanium dioxide, which has a narrow spectral range and absorbs less than 10% of visible light, and has limited air purification effect. In fact, the existing permeable ground materials with air purification effect have limited purification effects and need to be further improved. Summary of the invention
[0003] The purpose of the present application is to provide an environmentally friendly ecological water filter board that can purify the air and a preparation method thereof. The environmentally friendly ecological water filter board has a high efficiency air purification effect while ensuring strength, wear resistance and water permeability.
[0004] On the one hand, the present application provides an environmentally friendly ecological water filter board capable of purifying air, which is formed by mixing raw materials and then pressing them as a whole, wherein the raw materials include: 300 to 380 parts by weight of aggregate, 50 to 70 parts by weight of a cement-based composite adhesive modified by a polymer and a resin, and 10 to 30 parts by weight of a composite purifier;
[0005] The composite purifier is a zinc oxide-titanium dioxide-graphene nanocomposite powder, which is prepared by the following method:
[0006] (1) dissolving zinc acetate and sodium carbonate in water, adding graphene powder, stirring for 2 to 3 hours, filtering to obtain a precipitate, washing and drying the precipitate in turn to obtain a precursor, and calcining the precursor at 500 to 600° C. for 1 to 2 hours to obtain a zinc oxide-graphene nanocomposite powder;
[0007] (2) mixing the zinc oxide-graphene nanocomposite powder with anhydrous ethanol and glacial acetic acid, adding tetrabutyl titanate for hydrolysis, evaporating in a water bath, and drying to obtain the zinc oxide-titanium dioxide-graphene nanocomposite powder;
[0008] (3) ball milling the zinc oxide-titanium dioxide-graphene nanocomposite powder;
[0009] In step (1), the mass ratio of zinc acetate, sodium carbonate and graphene powder is 22:10 to 15:44;
[0010] In step (2), the mass ratio of zinc oxide-graphene nanocomposite powder to tetrabutyl titanate is 30:6-9.
[0011] In some specific embodiments, the aggregate is quartz sand with a particle size of 40 to 60 meshes.
[0012] In some specific embodiments, the polymer and resin modified cement-based composite binder is composed of a resin base, a cement-based material, and a nano-level pure acrylic emulsion in a weight ratio of 3-5:10-20:2-4; wherein: every 100 parts by weight of the resin base includes: 50-70 parts by weight of asparagus polyurea resin, 20-40 parts by weight of aliphatic isocyanate, and 5-10 parts by weight of elastomeric polyurea curing agent; every 100 parts by weight of the cement-based material includes: 50-60 parts by weight of cement, 12-20 parts by weight of a strengthening and expansion agent, 6-30 parts by weight of stone powder, 0-10 parts by weight of a pigment, 1-2 parts by weight of a dispersant, 1-2 parts by weight of a defoaming agent, 1-2 parts by weight of a water retaining agent, and 1-3 parts by weight of a setting regulator.
[0013] In some specific embodiments, the raw materials include: 350-380 parts by weight of aggregate, 60-70 parts by weight of a polymer and resin modified cement-based composite binder, and 16-24 parts by weight of a composite purifier.
[0014] On the other hand, the present application provides a method for preparing an environmentally friendly ecological water filter board capable of purifying air, comprising:
[0015] (1) taking aggregate, polymer, resin-modified cement-based composite binder and composite purifier according to weight, putting them into a stirring pot and stirring and mixing, then adding mixing water and continuing to stir to obtain a mixture;
[0016] (2) Spreading the mixture in a mold and compacting it into shape by static pressure;
[0017] (3) After maintenance, an environmentally friendly ecological water filter board is obtained.
[0018] In some specific embodiments, the curing includes: first curing in a curing room at a temperature of 30°C to 40°C for 5 to 7 days, and then curing outdoors at room temperature for 14 to 28 days.
[0019] Compared with the prior art, this application has the following advantages and beneficial effects:
[0020] (1) The environmentally friendly ecological water filter board of the present application has excellent compressive strength, wear resistance and water permeability, and also has an air purification function, which can purify harmful gases such as nitrogen oxides and toluene in the air, and can be widely used in municipal roads, communities, parks, pedestrian streets, etc.
[0021] (2) The present application adds a zinc oxide-titanium dioxide-graphene nanocomposite purifier prepared by a specific method to the raw materials of traditional prefabricated sand-based permeable materials, which does not affect the compressive strength, wear resistance and water permeability of the permeable materials. At the same time, the nanocomposite purifier can also oxidize harmful gases such as toluene and nitrogen oxides in the air through photocatalysis, and decompose the harmful gases into carbon dioxide and water, thereby achieving the effect of purifying the air.
[0022] (3) Based on conventional sand-based permeable bricks, the present application adopts integral molding to make an ecological water filter board, removing the permeable concrete bottom layer of the conventional sand-based bricks. The main material composition of the main body includes ultrafine aggregate and composite binder. The use of composite binder and the design of removing the permeable concrete bottom layer can effectively avoid the alkali efflux problem of cement-based materials. Ultrafine aggregate is used as the whole, and the permeable pores formed are very small. Pollutants will only stay on the surface of the material and will not penetrate into the pores, which will not cause blockage and is also conducive to later maintenance. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and beneficial effects of the present application more clear, the present application is further described in detail below in conjunction with embodiments.
[0024] The present application provides an environmentally friendly ecological water filter board capable of purifying air, which is formed by pressing as a whole; wherein: the raw materials include: 300 to 380 parts by weight of aggregate, 50 to 70 parts by weight of a cement-based composite adhesive modified by a polymer and a resin, and 10 to 30 parts by weight of a composite purifier;
[0025] In some specific embodiments, the raw materials include: 350-380 parts by weight of aggregate, 60-70 parts by weight of a polymer and resin modified cement-based composite binder, and 16-24 parts by weight of a composite purifier.
[0026] In some specific embodiments, the polymer and resin modified cement-based composite adhesive adopts the applicant's patented product, see the Chinese patent with announcement number CN113831077B, which is an adhesive for permeable paving materials, obtained by modifying the cement-based adhesive with a resin base and an acrylic emulsion.
[0027] The composite purifier is a zinc oxide-titanium dioxide-graphene nanocomposite powder, which is prepared by the following method;
[0028] (1) dissolving zinc acetate and sodium carbonate in water, adding graphene powder and mixing, stirring for 2 to 3 hours, reacting zinc acetate and sodium carbonate to obtain a precipitate, washing the precipitate with water and drying it in turn to obtain a precursor, and calcining the precursor at 500 to 600° C. for 1 to 2 hours to obtain zinc oxide-graphene nanocomposite powder;
[0029] In this step, zinc acetate and sodium carbonate react, and the reaction products include zinc hydroxide precipitate and soluble sodium salt. The zinc hydroxide precipitate is decomposed into zinc oxide by roasting. The roasting temperature of 500-600° C. is selected to more easily decompose the nano-sized zinc oxide.
[0030] (2) mixing the zinc oxide-graphene nanocomposite powder with anhydrous ethanol and glacial acetic acid, adding tetrabutyl titanate to hydrolyze for 0.5 to 1 h, evaporating to dryness in a water bath, and drying to obtain the zinc oxide-titanium dioxide-graphene nanocomposite powder;
[0031] (3) The zinc oxide-titanium dioxide-graphene nanocomposite powder is ball milled.
[0032] In this specific embodiment, in step (1), the mass ratio of zinc acetate, sodium carbonate and graphene powder is 22:10-15:44; in step (2), the mass ratio of zinc oxide-graphene nanocomposite powder, glacial acetic acid and tetrabutyl titanate is 30:2-5:6-9, and the usage ratio of tetrabutyl titanate and anhydrous ethanol is 6-9g:80-100mL.
[0033] In this application, zinc oxide and titanium dioxide play a photocatalytic role, and photogenerated electrons are transferred through the interface formed by the semiconductor material (zinc oxide and titanium dioxide) and graphene. Too little graphene will make it difficult for the semiconductor material to fully contact the graphene, thereby affecting the transfer of photogenerated electrons; since graphene itself has basically no photocatalytic effect, too much graphene will affect the photocatalytic effect of zinc oxide and titanium dioxide. Therefore, graphene should be used in a specific amount to further improve the air purification effect.
[0034] In this specific embodiment, the preparation method of the above-mentioned environmentally friendly ecological water filter plate includes:
[0035] (1) Aggregate, polymer, resin-modified cement-based composite binder and composite purifier are taken in parts by weight, put into a stirring pot, and stirred and mixed, and then mixing water is added and stirred continuously to obtain a mixture; the amount of mixing water is conventionally used. In some specific embodiments, the amount of mixing water is 3% to 8% by weight of the raw material mixture.
[0036] (2) placing the mixture in a mold and compacting it into shape using static pressure;
[0037] (3) After maintenance, an environmentally friendly ecological water filter board is obtained.
[0038] Several embodiments and comparative examples are provided below. It should be noted that in the embodiments and comparative examples, the aggregate used is quartz sand with a particle size of 40 to 60 mesh, and the particle size of the graphene powder used is 3 to 9 nm.
[0039] The polymer and resin modified cement-based composite adhesive adopts the adhesive in the Chinese patent with the announcement number CN113831077B. Specifically, the product of Example 1 in the Chinese patent is adopted, and the specific preparation method is as follows:
[0040] (1) Preparation of cement-based materials:
[0041] Weigh the raw materials: 50 parts by weight of PI52.5 type silicate cement, 12 parts by weight of strengthening expansion agent, 30 parts by weight of stone powder, 4 parts by weight of iron oxide red pigment, 1 part by weight of dispersant, 1 part by weight of P8850 defoamer, 1 part by weight of wood fiber, and 1 part by weight of setting agent.
[0042] (2) Preparation of resin base material:
[0043] Weigh the raw materials: 50 parts by weight of aspartame polyurea resin, 40 parts by weight of aliphatic isocyanate, and 10 parts by weight of elastomeric polyurea curing agent.
[0044] (3) Preparation of adhesive:
[0045] According to the weight ratio of resin base material: cement-based material: nano-grade pure acrylic emulsion = 3:10:2, the cement-based material and the nano-grade pure acrylic emulsion are first mixed and stirred for 3 minutes to a uniform slurry state, and then the mixed resin base is added thereto, and the mixing and stirring is continued for 3 minutes to obtain a polymer and resin modified cement-based composite adhesive.
[0046] Example 1
[0047] The environmentally friendly ecological water filter board of this embodiment is formed by integral pressing; wherein the raw materials include: 350 parts by weight of quartz sand, 60 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 16 parts by weight of a composite purifier.
[0048] The composite purifier is a zinc oxide-titanium dioxide-graphene nanocomposite powder, which is prepared by the following method:
[0049] (1) Dissolving zinc acetate and sodium carbonate in water, adding graphene powder, and stirring for 3 hours, filtering to obtain a white precipitate, repeatedly washing the precipitate with distilled water until the precipitate is neutral; then successively evaporating to dryness in a water bath and drying in an oven to obtain a precursor, placing the precursor in a muffle furnace, and calcining at 500° C. for 1 hour to obtain a zinc oxide-graphene nanocomposite powder;
[0050] (2) taking zinc oxide-graphene nanocomposite powder, anhydrous ethanol and glacial acetic acid and mixing them, then adding tetrabutyl titanate to hydrolyze, then evaporating to dryness in a water bath and drying in an oven to obtain zinc oxide-titanium dioxide-graphene nanocomposite powder;
[0051] (3) placing the zinc oxide-titanium dioxide-graphene nanocomposite powder into a ball mill and milling for 1 hour;
[0052] In step (1), the mass ratio of zinc acetate, sodium carbonate and graphene powder is 22:10:44; in step (2), the mass ratio of zinc oxide-graphene nanocomposite powder, glacial acetic acid and tetrabutyl titanate is 30:2:6, and the usage ratio of tetrabutyl titanate and anhydrous ethanol is 6g:80ml.
[0053] Example 2
[0054] The environmentally friendly ecological water filter board of this embodiment is formed by integral pressing; wherein the raw materials include: 360 parts by weight of quartz sand, 65 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 18 parts by weight of a composite purifier.
[0055] The composite purifier is a zinc oxide-titanium dioxide-graphene nanocomposite powder, which is prepared by the following method:
[0056] (1) Dissolving zinc acetate and sodium carbonate in water, adding graphene powder, and stirring for 3 hours, filtering to obtain a white precipitate, repeatedly washing the precipitate with distilled water until the precipitate is neutral; then successively evaporating to dryness in a water bath and drying in an oven to obtain a precursor, placing the precursor in a muffle furnace, and calcining at 500° C. for 1 hour to obtain a zinc oxide-graphene nanocomposite powder;
[0057] (2) taking zinc oxide-graphene nanocomposite powder, anhydrous ethanol and glacial acetic acid and mixing them, then adding tetrabutyl titanate to hydrolyze, then evaporating to dryness in a water bath and drying in an oven to obtain zinc oxide-titanium dioxide-graphene nanocomposite powder;
[0058] (3) placing the zinc oxide-titanium dioxide-graphene nanocomposite powder into a ball mill and milling for 1 hour;
[0059] In step (1), the mass ratio of zinc acetate, sodium carbonate and graphene powder is 22:13:44; in step (2), the mass ratio of zinc oxide-graphene nanocomposite powder, glacial acetic acid and tetrabutyl titanate is 30:3:7, and the amount ratio of tetrabutyl titanate and anhydrous ethanol is 7g:90ml.
[0060] Example 3
[0061] The environmentally friendly ecological water filter board of this embodiment is formed by integral pressing; wherein the raw materials include: 380 parts by weight of quartz sand, 70 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 24 parts by weight of a composite purifier.
[0062] The composite purifier is a zinc oxide-titanium dioxide-graphene nanocomposite powder, which is prepared by the following method:
[0063] (1) Dissolving zinc acetate and sodium carbonate in water, adding graphene powder, and stirring for 3 hours, filtering to obtain a white precipitate, repeatedly washing the precipitate with distilled water until the precipitate is neutral; then successively evaporating to dryness in a water bath and drying in an oven to obtain a precursor, placing the precursor in a muffle furnace, and calcining at 500° C. for 1 hour to obtain a zinc oxide-graphene nanocomposite powder;
[0064] (2) taking zinc oxide-graphene nanocomposite powder, anhydrous ethanol and glacial acetic acid and mixing them, then adding tetrabutyl titanate to hydrolyze, then evaporating to dryness in a water bath and drying in an oven to obtain zinc oxide-titanium dioxide-graphene nanocomposite powder;
[0065] (3) placing the zinc oxide-titanium dioxide-graphene nanocomposite powder into a ball mill and milling for 1 hour;
[0066] In step (1), the mass ratio of zinc acetate, sodium carbonate and graphene powder is 22:15:44; in step (2), the mass ratio of zinc oxide-graphene nanocomposite powder, glacial acetic acid and tetrabutyl titanate is 30:5:9, and the usage ratio of tetrabutyl titanate and anhydrous ethanol is 9g:100ml.
[0067] Comparative Example 1
[0068] The environmentally friendly ecological water filter board of this comparative example is formed by integral pressing; wherein the raw materials include: 350 parts by weight of quartz sand, 60 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 16 parts by weight of a single-component purifier.
[0069] The single-component purifier is nano zinc oxide, which is made by the following method:
[0070] Zinc acetate and sodium carbonate were dissolved in water at a weight ratio of 22:10, and the mixture was stirred for 3 hours. A white precipitate was obtained by filtration, and the precipitate was repeatedly washed with distilled water until it was neutral. The precipitate was then evaporated in a water bath and dried in an oven to obtain a precursor. The precursor was placed in a muffle furnace and calcined at 500°C for 1 hour to obtain nano zinc oxide.
[0071] Comparative Example 2
[0072] The environmentally friendly ecological water filter board of this comparative example is formed by integral pressing; wherein the raw materials include: 360 parts by weight of quartz sand, 65 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 18 parts by weight of a single-component purifier.
[0073] The single-component purifier is nano-titanium dioxide, which is made by the following method:
[0074] Anhydrous ethanol, glacial acetic acid and tetrabutyl titanate are mixed to hydrolyze the tetrabutyl titanate, and then evaporated in a water bath and dried in an oven to obtain nano titanium dioxide; wherein the mass ratio of glacial acetic acid to tetrabutyl titanate is 1:3, and the mass ratio of tetrabutyl titanate to anhydrous ethanol is 3g:90ml.
[0075] Comparative Example 3
[0076] The environmentally friendly ecological water filter board of this comparative example is formed by integral pressing; wherein the raw materials include: 380 parts by weight of quartz sand, 70 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 24 parts by weight of a composite purifier.
[0077] The composite purifier is a zinc oxide-titanium dioxide nanocomposite powder, which is prepared by the following method:
[0078] (1) Dissolving zinc acetate and sodium carbonate in water at a weight ratio of 22:10, stirring for 3 hours, filtering to obtain a white precipitate, repeatedly washing the precipitate with distilled water until the precipitate is neutral; then evaporating to dryness in a water bath and drying in an oven to obtain a precursor, placing the precursor in a muffle furnace, and calcining at 500° C. for 1 hour to obtain nano zinc oxide;
[0079] (2) taking nano zinc oxide, anhydrous ethanol and glacial acetic acid and mixing them, then adding tetrabutyl titanate to hydrolyze, then evaporating in a water bath and drying in an oven to obtain zinc oxide-titanium dioxide nanocomposite powder; wherein the mass ratio of nano zinc oxide, glacial acetic acid and tetrabutyl titanate is 10:5:9, and the mass ratio of tetrabutyl titanate and anhydrous ethanol is 9g:100ml;
[0080] (3) The zinc oxide-titanium dioxide nanocomposite powder was placed in a ball mill and ball milled for 1 hour.
[0081] Comparative Example 4
[0082] The environmentally friendly ecological water filter board of this comparative example is formed by integral pressing; wherein the raw materials include: 350 parts by weight of quartz sand, 60 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 16 parts by weight of a composite purifier.
[0083] The composite purifier is a zinc oxide-graphene nanocomposite powder, which is prepared by the following method:
[0084] (1) Dissolving zinc acetate and sodium carbonate in water, adding graphene powder, and stirring for 3 hours, filtering to obtain a white precipitate, repeatedly washing the precipitate with distilled water until the precipitate is neutral; then successively evaporating to dryness in a water bath and drying in an oven to obtain a precursor, placing the precursor in a muffle furnace, and calcining at 500° C. for 1 hour to obtain zinc oxide-graphene nanocomposite powder; wherein the mass ratio of zinc acetate, sodium carbonate, and graphene powder is 22:10:44;
[0085] (2) The zinc oxide-graphene nanocomposite powder was placed in a ball mill and ball milled for 1 hour.
[0086] Comparative Example 5
[0087] The environmentally friendly ecological water filter board of this comparative example is formed by integral pressing; wherein the raw materials include: 350 parts by weight of quartz sand, 60 parts by weight of a cement-based composite adhesive modified by a polymer and resin, and 16 parts by weight of a composite purifier.
[0088] The composite purifier is titanium dioxide-graphene nanocomposite powder, which is prepared by the following method:
[0089] (1) taking graphene powder, anhydrous ethanol and glacial acetic acid, mixing them, adding tetrabutyl titanate to hydrolyze them, and then evaporating them in a water bath and drying them in an oven to obtain titanium dioxide-graphene nanocomposite powder; wherein the mass ratio of graphene powder, glacial acetic acid and tetrabutyl titanate is 20:2:6, and the mass ratio of tetrabutyl titanate to anhydrous ethanol is 6g:80ml;
[0090] (2) The titanium dioxide-graphene nanocomposite powder was placed in a ball mill and ball milled for 1 hour.
[0091] Comparative Example 6
[0092] The environmentally friendly ecological water filter board of this comparative example is formed by integral pressing; wherein the raw materials include: 350 parts by weight of quartz sand, 60 parts by weight of a cement-based composite adhesive modified by a polymer and resin, 4.728 parts by weight of nano zinc oxide, 1.816 parts by weight of nano titanium dioxide, and 9.456 parts by weight of graphene.
[0093] In this comparative example, nano zinc oxide is prepared by the method disclosed in comparative example 1, and nano titanium dioxide is prepared by the method disclosed in comparative example 2.
[0094] The environmentally friendly ecological water filter plates in the above embodiments and comparative examples are prepared by the following method:
[0095] (1) Quartz sand, polymer and resin-modified cement-based composite binder and purifier are taken by weight, put into a stirring pot, and stirred for 1 minute using a mortar mixer. The stirring is continued and mixing water is slowly poured in. After the mixing water is added, the stirring is continued for 3 minutes. At this time, the raw materials are evenly mixed and in a fine agglomerate state to obtain a mixture; wherein the amount of mixing water is 5% of the raw material mixture;
[0096] (2) placing the mixture into a mold and compacting it using a static pressure molding machine;
[0097] (3) After being placed in a 30°C curing room for 7 days, it is sent to the outdoors for curing at room temperature until it becomes an ecological water filter board after 28 days.
[0098] The ecological water filter plates of the embodiments and comparative examples were tested for performance as follows:
[0099] 1. Compressive strength: Tested in accordance with Appendix A of JC / T945-2005 "Permeable Brick Industry Standard";
[0100] 2. Wear resistance: Test the length of the wear pit according to GB / T12988 "Test method for wear resistance of inorganic floor materials";
[0101] 3. Water permeability coefficient: tested according to the testing method in JC / T945-2005 "Permeable Brick Industry Standard";
[0102] 4. NOx reduction rate: The ecological water filter plates were placed in sealed glass containers of the same volume. The initial concentration of nitrogen oxides in each glass container was 350 mg / L. After the ecological water filter plates were placed for 24 hours, the concentration of nitrogen oxides in the glass container was tested by the naphthylethylenediamine hydrochloride spectrophotometry, and the NOx reduction rate was calculated;
[0103] 5. Place the ecological water filter plate in a sealed glass box of the same volume, and simulate an environment with a toluene pollution concentration of 200μg / L in the glass box. Place each glass box under the same lighting conditions, and connect the air pressure balance port at the bottom of the glass box to the water tank to maintain the air pressure and polluted gas concentration in the glass box during sampling. Turn on the convection fan to keep the gas concentration in each part of the glass box equal. After the polluted gas is introduced to the starting concentration, close the air inlet and start the photodegradation process. After that, use a micro-sampling pump to sample the air in the glass box, and then use gas chromatography to determine the change in gas content during the degradation process. Calculate the toluene removal rate according to the formula Among them, C 0 Indicates the initial concentration of toluene when degradation begins, unit: μg / m 3 ; C t Indicates the equilibrium concentration of pollutant gas when the test is completed, unit: μg / m 3 ; The test time of all embodiments and comparative examples is 6h.
[0104] Table 1 Performance test data of ecological water filter board of embodiment and comparative example
[0105]
[0106]
[0107] It can be seen from the performance test data in Table 1 that the compressive strength, wear resistance and water permeability of the ecological water filter plates of Examples 1 to 3 and Comparative Examples 1 to 6 are equivalent, but the NOx reduction rate and toluene removal rate of the ecological water filter plates of Examples 1 to 3 are significantly higher, that is, the air purification effect of the ecological water filter plates of Examples 1 to 3 is more excellent. In Comparative Example 1, only a single-component purifier of nano zinc oxide is used in the ecological water filter plate, and only a single-component purifier of nano titanium dioxide is used in the ecological water filter plate of Comparative Example 2. In Comparative Example 3, a zinc oxide-titanium dioxide nanocomposite purifier is used in the ecological water filter plate. Compared with the use of a single-component purifier, the air purification effect of the zinc oxide-titanium dioxide nanocomposite purifier is slightly improved. In Comparative Example 4, a zinc oxide-graphene nanocomposite purifier is used in the ecological water filter plate, and a titanium dioxide-graphene nanocomposite purifier is used in the ecological water filter plate of Comparative Example 5. Compared with Comparative Examples 1 and 2 that only use a single-component purifier, the air purification effect of graphene only compounded with zinc oxide or titanium dioxide is also slightly improved. However, the air purification effect produced by the combination of zinc oxide, titanium dioxide and graphene is significantly improved.
[0108] Although the purifier in Comparative Example 6 includes zinc oxide, titanium dioxide and graphene, it is actually a mixture of zinc oxide, titanium dioxide and graphene, and is not compounded. The purifiers in Examples 1 to 3 are zinc oxide-titanium dioxide-graphene nanocomposite powders prepared by a specific method. Compared with the ecological water filter board in Comparative Example 6, the NOx reduction rate of the ecological water filter board in Example 1 is increased by about 24%, and the toluene removal rate is increased by about 13%, and the purification effect is significantly improved.
[0109] The applicant believes that the mechanism by which the present application can produce the above technical effects is:
[0110] The band gap of zinc oxide is 3.37eV, and the band gap of titanium dioxide is 3.0eV to 3.2eV. When zinc oxide and titanium dioxide are compounded, the wide-bandgap zinc oxide can promote the photogenerated carriers of narrow-bandgap titanium dioxide and inhibit the recombination of electron holes, thereby improving the photocatalytic efficiency. At the same time, it is also compounded with graphene. The conduction band energy levels of zinc oxide and titanium dioxide are higher than the Fermi level of graphene. Photogenerated electrons are easily transferred from semiconductor materials (i.e., zinc oxide and titanium dioxide) to graphene through the interface formed by the semiconductor material (i.e., zinc oxide and titanium dioxide) and graphene. The two-dimensional planar structure of graphene composed of a huge conjugated system can quickly transfer photogenerated electrons to the target reactant at an extremely high carrier migration rate. At the same time, it also prolongs the average free path of photogenerated electrons. Photogenerated electrons participate in the formation of highly active free radicals (such as radical free radicals and peroxy free radicals), non-selectively oxidatively degrade organic pollutants, and photocatalytically sterilize, thereby improving the efficiency of pollutant degradation.
[0111] Note that the above are only preferred embodiments of the present application and the technical principles used. Those skilled in the art will understand that the present application is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the protection scope of the present application. Therefore, although the present application is described in more detail through the above embodiments, the present application is not limited to the above embodiments, and may also include more other equivalent embodiments without departing from the concept of the present application, all of which belong to the protection scope of the present application.
Claims
1. An environmentally friendly ecological water filter board that can purify air, characterized by: The raw materials are mixed and pressed as a whole, wherein the raw materials include: 300 to 380 parts by weight of aggregate, 50 to 70 parts by weight of a cement-based composite adhesive modified by a polymer and a resin, and 10 to 30 parts by weight of a composite purifier; The composite purifier is a zinc oxide-titanium dioxide-graphene nanocomposite powder, which is prepared by the following method: (1) dissolving zinc acetate and sodium carbonate in water, adding graphene powder, stirring for 2 to 3 hours, filtering to obtain a precipitate, washing and drying the precipitate in turn to obtain a precursor, and calcining the precursor at 500 to 600° C. for 1 to 2 hours to obtain a zinc oxide-graphene nanocomposite powder; (2) mixing the zinc oxide-graphene nanocomposite powder with anhydrous ethanol and glacial acetic acid, adding tetrabutyl titanate for hydrolysis, evaporating in a water bath, and drying to obtain the zinc oxide-titanium dioxide-graphene nanocomposite powder; (3) ball milling the zinc oxide-titanium dioxide-graphene nanocomposite powder; In step (1), the mass ratio of zinc acetate, sodium carbonate and graphene powder is 22:10 to 15:44; In step (2), the mass ratio of zinc oxide-graphene nanocomposite powder to tetrabutyl titanate is 30:6-9.
2. The environmentally friendly ecological water filter board capable of purifying air as claimed in claim 1 is characterized by: The aggregate is quartz sand with a particle size of 40 to 60 meshes.
3. The environmentally friendly ecological water filter board capable of purifying air as claimed in claim 1 is characterized by: The polymer and resin modified cement-based composite binder is composed of a resin base material, a cement-based material, and a nano-level pure acrylic emulsion in a weight ratio of 3-5:10-20:2-4; wherein: every 100 weight parts of the resin base material comprises: 50-70 weight parts of asparagine polyurea resin, 20-40 weight parts of aliphatic isocyanate, and 5-10 weight parts of elastomeric polyurea curing agent; every 100 weight parts of the cement-based material comprises: 50-60 weight parts of cement, 12-20 weight parts of strengthening expansion agent, 6-30 weight parts of stone powder, 0-10 weight parts of pigment, 1-2 weight parts of dispersant, 1-2 weight parts of defoamer, 1-2 weight parts of water retaining agent, and 1-3 weight parts of setting regulator.
4. The environmentally friendly ecological water filter board capable of purifying air as claimed in claim 1 is characterized by: The raw materials include: 350-380 parts by weight of aggregate, 60-70 parts by weight of a cement-based composite binder modified by a polymer and a resin, and 16-24 parts by weight of a composite purifier.
5. The method for preparing the environmentally friendly ecological water filter board according to any one of claims 1 to 4, characterized in that: include: (1) taking aggregate, polymer, resin-modified cement-based composite binder and composite purifier according to weight, putting them into a stirring pot and stirring and mixing, then adding mixing water and continuing to stir to obtain a mixture; (2) Spreading the mixture in a mold and compacting it into shape by static pressure; (3) After maintenance, an environmentally friendly ecological water filter board is obtained.
6. The method for preparing the environmentally friendly ecological water filter board according to claim 5, characterized in that: The curing comprises: first curing in a curing room at a temperature of 30° C. to 40° C. for 5 to 7 days, and then curing outdoors at room temperature for 14 to 28 days.
Citation Information
Patent Citations
An adhesive for permeable pavement materials and its application
CN113831077B
Stone-imitated light water-permeable plate and preparation method thereof
CN110423063A
Adhesive for water-permeable paving material and application of adhesive
CN113831077A